Carbonic Anhydrases and Their Biotechnological Applications - Robert McKenna; Sonika Gill; Christopher D. Boone; Andrew Habibzadegan (Biomolecules, 2013)
The carbonic anhydrases (CAs) are mostly zinc-containing metalloenzymes which catalyze the reversible hydration/dehydration of carbon dioxide/bicarbonate. The CAs have been extensively studied because of their broad physiological importance in all kingdoms of life and clinical relevance as drug targets. In particular, human CA isoform II (HCA II) has a catalytic efficiency of 108 M−1 s−1, approaching the diffusion limit. The high catalytic rate, relatively simple procedure of expression and purification, relative stability and extensive biophysical studies of HCA II has made it an exciting candidate to be incorporated into various biomedical applications such as artificial lungs, biosensors and CO2 sequestration systems, among others. This review highlights the current state of these applications, lists their advantages and limitations, and discusses their future development.